PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO TUTORIAL PEMBUATAN MOODBOARD FASE F SMK NEGERI 3 BLITAR - Sefirlia Sari, Dynis Nova; Nahari, Inty; Arifiana, Deny; Yuniati, Mita (Jurnal Socia Akademika, 2025)
This study's objective is to present the results, material viability, student reactions, and product trial outcomes from the creation of an instructional video learning resource on the Moodboard creation process for SMK Negeri 3 Blitar. A research and development methodology Both qualitative and quantitative methods were applied.to perform the study at SMK Negeri 3 Blitar. 34 pupils from the sample were drawn from the XI Fashion Design class. The material and media developed went through an expert validation process, which showed that the feasibility results of the material and media interpreted as being very practical, with average score percentages of 96% and 95%, respectively. Questionnaires addressing language, use, medium, and content were used to gather data. The student responses yielded an average score percentage of 93%, which was interpreted as extremely good. The outcomes of the product trial showed an average score of 95 or a completion rate of 100%, indicating positive results in the development of students competency in creating Moodboards.